Comparison of intermediate Lithuanian mathematics programs with the 1912 Viurtemberg mathematics program in Germany - Ragalytė, Birutė; Paukštienė, Alma (Lietuvos matematikos rinkinys, 2019)
The article compares interwar Lithuanian mathematics programs with Württemberg mathematics programs in German land. The inﬂuence of Klein’s ideas on the content of the programs is presented.
Keywords: mathematics program; Klein idea; interwar Lithuanian mathematics